RANCANG BANGUN SISTEM INFORMASI HIMPUNAN ALUMNI MAHASISWA STIKOM YOS SUDARSO (HAMSYS) PURWOKERTO BERBASIS WEBSITE - Carolina Ety Widjayanti; Brilian Amalsha Katigo; Rosalina Yani Widiastuti; Antonius Ary Setyawan (Electro Luceat, 2023)
STIKOM Yos Sudarso is a college that annually produces graduates. For these graduates, a tracing process is needed to evaluate the curriculum to improve their quality. However, the recording of alumni data that still use excel, tracing studies that still use google forms where the contents have not been adjusted to the Kemdikbud template, and the job vacancies that are only shared through WhatsApp groups are still obstacles in the process of improving alumni quality. Therefore, a website-based Information System for STIKOM Yos Sudarso Student Alumni Association (HAMSYS) Purwokerto was developed using a prototype method, PHP programming language, and MySQL database. The hypotheses were tested using paired sample t-test, while the system was tested using a black box and white box test. In addition, a system evaluation was carried out through benefit testing based on ISO 25010. From the benefits test, the percentage of "agree" and "strongly agree" answers were 96,23% on Functional Suitability, 90,33% on Performance Efficiency, 97,68% on Usability, 92.08% on Reliability, and 92,9% on Maintainability. Based on the test results, it can be concluded that the HAMSYS system has been successfully developed with good quality and can simplify also speed up the tracer study reporting process.